CODE CHOICE USED BY CHIYU TAMADE (CHU2) CHARACTER IN THE ANIME “BANG DREAM! SEASON 2 EP 3, 8, AND 9” - Fanzial Ulhaq Roufur Rochim; Dona Rahayu Sugiharti (Universitas 17 Agustus 1945 Surabaya, 2022)
In the field of Sociolinguistics, phenomenons of language use such as code-switching and code-mixing are often found in our daily lives. BanG Dream is a multimedia project that focuses on music-themed media products that include manga, anime series, game, musical CD’s and live concerts. In the anime series, BanG Dream, a certain character named Chu2 has interesting background that allow her to have the tendency to perform use of code-switching and code-mixing. This paper aims to find out the types of code-switching and code-mixing found in the utterances of Chu2 in the BanG Dream anime series season 2 episode 3, 8, and 9 and analyze factors affecting doing code switching and code mixing. The research was conducted using a qualitative method through observation to find out the types and the reason for every code-switching and code-mixing found in Chu2’s utterances. The findings showed that there were a total of 23 data, including 13 data of code-switching and 10 data of code-mixing. Three types of code-switching used by Chu2 were tag switching, inter-sentential switching and intra-sentential switching. Meanwhile, there can only be found one type of code-mixing used by Chu2 in her utterances which was insertion. The findings showed that the reason Chu2 performs the phenomenon of code-switching and code-mixing was because of her preferred language to speak English instead of her mother language Japanese, and her social identity as an international high school student which acts as a background to her tendency to constantly switch and mix between Japanese and English because she used to speak English in her school.